Strategi Pengembangan Usaha Sarang Walet di Kecamatan Abeli Kota Kendari - Hasanah, Uswatun; Bafadal, Azhar; Zani, Munirwan (Jurnal Social Economic of Agriculture, 2024)
Business competition is one of the main threats faced by swiftlet nest entrepreneurs, necessitating the implementation of appropriate strategies to enhance competitiveness. This study aims to design strategies for the development of swiftlet nest businesses. Qualitative and quantitative descriptive analysis methods were employed to describe the internal and external conditions of the swiftlet nest business, while SWOT analysis was used to formulate alternative strategies for its development. The results of the study indicate that the strategies that can be implemented by swiftlet nest entrepreneurs align with a strength-opportunity approach, involving the following steps: (1) Utilizing modern technology to advance and develop the business both offline and online, thereby creating effective marketing channels; (2) Selecting strategic business locations to ensure the comfort and habitation of swiftlets, resulting in higher-quality and more beneficial nests; and (3) Optimizing the use of capital, which plays a critical role in maintaining the financial stability of swiftlet nest entrepreneurs.